Menaquinone-7 Supplementation Improves Osteogenesis in Pluripotent Stem Cell Derived Mesenchymal Stem Cells - Akbulut, Asim Cengiz; Wasilewski, Grzegorz B.; Rapp, Nikolas; Forin, Francesco; Singer, Heike; Czogalla-Nitsche, Katrin J.; Schurgers, Leon J. (Frontiers in Cell and Developmental Biology, 2021)
Development of clinical stem cell interventions are hampered by immature cell progeny under current protocols. Human mesenchymal stem cells (hMSCs) are characterised by their ability to self-renew and differentiate into multiple lineages. Generating hMSCs from pluripotent stem cells (iPSCs) is an attractive avenue for cost-efficient and scalable production of cellular material. In this study we generate mature osteoblasts from iPSCs using a stable expandable MSC intermediate, refining established protocols. We investigated the timeframe and phenotype of cells under osteogenic conditions as well as the effect of menaquinone-7 (MK-7) on differentiation. From day 2 we noted a significant increase in RUNX2 expression under osteogenic conditions with MK-7, as well as decreases in ROS species production, increased cellular migration and changes to dynamics of collagen deposition when compared to differentiated cells that were not treated with MK-7. At day 21 OsteoMK-7 increased alkaline phosphatase activity and collagen deposition, as well as downregulated RUNX2 expression, suggesting to a mature cellular phenotype. Throughout we note no changes to expression of osteocalcin suggesting a non-canonical function of MK-7 in osteoblast differentiation. Together our data provide further mechanistic insight between basic and clinical studies on extrahepatic activity of MK-7. Our findings show that MK-7 promotes osteoblast maturation thereby increasing osteogenic differentiation.